Searching for Dragons - Patricia C. Wrede (United Kingdom Point Fantasy, 1992)
Expected by his advisors to take a princess as his bride, young King Mendanbar declines, until he meets Princess Cimorene, a young woman who ran off with dragons in order to avoid an unwanted betrothal
Keywords: Fantasy -- Fantasy